2017
DOI: 10.1002/ecm.1265
|View full text |Cite
|
Sign up to set email alerts
|

Alongshore variation in barnacle populations is determined by surf zone hydrodynamics

Abstract: Abstract. Larvae in the coastal ocean are transported toward shore by a variety of mechanisms. Crossing the surf zone is the last step in a shoreward migration and surf zones may act as semipermeable barriers altering delivery of larvae to the shore. We related variation in the structure of intertidal barnacle populations to surf zone width (surf zone hydrodynamics proxy), wave height, alongshore wind stress (upwelling proxy), solar radiation, and latitude at 40 rocky intertidal sites from San Diego, Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
87
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 74 publications
4
87
1
Order By: Relevance
“…Whether recruiting larvae enter the surf zone depends on alongshore variation in surfzone hydrodynamics caused by the interaction of breaking waves with coastal morphology. Orders of magnitude more larvae occur in surf zones on gently sloping, rather than steep, shores due to the presence of bathymetric rip currents Shanks et al, 2017). The substantial inconsistencies between our results and the ecologically based dispersal estimates suggest that a higherresolution modeling effort, capable of resolving the additional physical processes in the coastal boundary layer and surf zone, is needed to accurately predict the dispersal of benthic larvae, the corresponding connectivity of benthic subpopulations, and the design of MPAs.…”
Section: Discussionmentioning
confidence: 58%
“…Whether recruiting larvae enter the surf zone depends on alongshore variation in surfzone hydrodynamics caused by the interaction of breaking waves with coastal morphology. Orders of magnitude more larvae occur in surf zones on gently sloping, rather than steep, shores due to the presence of bathymetric rip currents Shanks et al, 2017). The substantial inconsistencies between our results and the ecologically based dispersal estimates suggest that a higherresolution modeling effort, capable of resolving the additional physical processes in the coastal boundary layer and surf zone, is needed to accurately predict the dispersal of benthic larvae, the corresponding connectivity of benthic subpopulations, and the design of MPAs.…”
Section: Discussionmentioning
confidence: 58%
“…The absence of rip currents, the reflective nature of the narrow energetic surf zone and weaker undertow resulted in an exchange rate of surf zone water that was consistent with dissipative beaches when alongshore currents were present (Brown ). In a coastwide survey of 40 sites, recruitment was greater at dissipative than intermediate shores with rip currents and least at reflective shores and one dissipative shore that lacked rip currents (Shanks et al in press b ).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae and other zooplankters may enter the surf zone in near‐surface onshore wind‐driven currents, Stokes drift and internal waves, whereas those near the bottom may be transported shoreward by benthic streaming (Fujimura et al ; Shanks et al ; Navarrete et al ). Larval settlement and planktonic food may be greater on dissipative than reflective shores, and they may be greatest on dissipative and intermediate shores where rip currents increase exchange of water outside and inside the surf zone (Shanks et al in press b ). In turn, the subsidies of larvae and food determine the intensity of top‐down processes in communities (Menge et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual based biophysical models revealed that Stokes drift and benthic boundary layer streaming coupled with downward swimming in response to turbulence from waves facilitated onshore larval delivery beaches (Fujimura et al, 2013(Fujimura et al, , 2014(Fujimura et al, , 2017(Fujimura et al, , 2018. The striking differences in surfzone oceanography at dissipative and reflective shores predictably affect larval recruitment and productivity of inshore communities Shanks et al, 2017, in press) and appear to explain recruitment limitation at many sites in California Shanks et al, 2017;. Together with the above results on larval distributions in upwelling areas, this suggests a shift in paradigms from the past idea that upwelling necessarily limits recruitment to new ideas that recruitment limitation and population connectivity may be better explained by alongshore differences in surfzone circulation Morgan, in press).…”
Section: Discussionmentioning
confidence: 99%